2016
DOI: 10.1097/nmd.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Déjà Vu Experiences in Healthy Czech Adults

Abstract: The study examines the prevalence of déjà vu in healthy Czech adults and explores its relationships with a number of variables: age, sex, neuroticism, depression, the degree of irritability in the limbic system, perceived stress, and finally attachment avoidance and anxiety. The participants were 365 healthy adults ranging from 18 to 70 years recruited in the Czech Republic (mean age = 29.05; SD = 11.17) who filled out online questionnaires. Déjà vu experiences were reported by 324 (88.8%) of them. Persons who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, since studies reported no relations between déjà vu and negative affect [53], and no researches have been done, so far, on the relation between alexithymia and déjà vu, as suggested by Funkhouser and Schredl [54], additional research is highly desirable on déjà vu experiences, also via prospective measures, such as for example, diary keeping, and through studying whether the variables associated with déjà vu frequency also explain inter-individual differences in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, since studies reported no relations between déjà vu and negative affect [53], and no researches have been done, so far, on the relation between alexithymia and déjà vu, as suggested by Funkhouser and Schredl [54], additional research is highly desirable on déjà vu experiences, also via prospective measures, such as for example, diary keeping, and through studying whether the variables associated with déjà vu frequency also explain inter-individual differences in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of non-ictal déjà vu in healthy individuals, estimated by a random-effects model combining 10 studies ( 7 , 8 , 52 , 53 , 63 , 72 , 73 , 76 , 79 , 82 ), revealed a pooled proportion of 0.74 (95% CI [0.67, 0.79], p < 0.001; see Figure 2 for the forest plot). Considerable heterogeneity was observed among the study proportions ( I 2 = 96.14%, Q (df = 9) = 233.23, p < 0.001), suggesting inconsistency across the studies.…”
Section: Resultsmentioning
confidence: 99%
“… Funnel plot of non-ictal déjà vu prevalence in healthy individuals. This plot illustrates study-specific data points (numbered squares; 1 ( 52 ); 2 ( 53 ); 3 ( 63 ); 4 ( 72 ); 5 ( 73 ); 6 ( 7 ); 7 ( 76 ); 8 ( 8 ); 9 ( 79 ); 10 ( 82 )) alongside the pooled estimate from the random-effects (RE) model (dotted line) plotted against proportions on the x-axis and standard error on the y-axis. Proportions have been back-transformed from logit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations